Unified quantitative observation of coexisting volcanic sulfur dioxide and sulfate aerosols using ground-based Fourier transform infrared spectroscopy - P. Sellitto; H. Guermazi; H. Guermazi; H. Guermazi; E. Carboni; E. Carboni; E. Carboni; R. Siddans; M. Burton (Atmospheric Measurement Techniques, 2019)
We developed an optimal-estimation algorithm to simultaneously retrieve, for the first time, coexisting volcanic gaseous SO2 and sulfate aerosols (SA) from ground-based Fourier transform infrared (FTIR) observations. These effluents, both linked to magmatic degassing process and subsequent atmospheric evolution processes, have overlapping spectral signatures leading to mutual potential interferences when retrieving one species without considering the other. We show that significant overestimations may be introduced in SO2 retrievals if the radiative impact of coexistent SA is not accounted for, which may have impacted existing SO2 long-term series, e.g. from satellite platforms. The method was applied to proximal observations at Masaya volcano, where SO2 and SA concentrations, and SA acidity, were retrieved. A gas-to-particle sulfur partitioning of 400 and a strong SA acidity (sulfuric acid concentration: 65 %) were found, consistent with past in situ observations at this volcano. This method is easily exportable to other volcanoes to monitor magma extraction processes and the atmospheric sulfur cycle in the case of ash-free plumes.